2014
DOI: 10.1371/journal.pone.0095883
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Changes in Prosaposin Expression in the Rat Dentate Gyrus after Birth

Abstract: Neurogenesis in the hippocampal dentate gyrus occurs constitutively throughout postnatal life. Adult neurogenesis includes a multistep process that ends with the formation of a postmitotic and functionally integrated new neuron. During adult neurogenesis, various markers are expressed, including GFAP, nestin, Pax6, polysialic acid-neural cell adhesion molecule (PSA-NCAM), neuronal nuclei (NeuN), doublecortin, TUC-4, Tuj-1, and calretinin. Prosaposin is the precursor of saposins A–D; it is found in various orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
(67 reference statements)
0
1
0
Order By: Relevance
“…PSAP is suggested to be an essential neurotrophic factor since its secretion stimulates proliferation and maturation of immature neurons in the hippocampus DG, as well as provides protection against apoptosis. It was reported that deficiency of PSAP precedes massive neuronal loss in neurotoxic environments (Morishita et al, 2014 ; Nabeka et al, 2017 ).…”
Section: Focus On Msc-derived Exosomes and Their Role In Neuroplasticmentioning
confidence: 99%
“…PSAP is suggested to be an essential neurotrophic factor since its secretion stimulates proliferation and maturation of immature neurons in the hippocampus DG, as well as provides protection against apoptosis. It was reported that deficiency of PSAP precedes massive neuronal loss in neurotoxic environments (Morishita et al, 2014 ; Nabeka et al, 2017 ).…”
Section: Focus On Msc-derived Exosomes and Their Role In Neuroplasticmentioning
confidence: 99%